Role of Dexmedetomidine by Improving Sleep Quality and Pain Control in Covid-19 Patients - Maliha Khalid; Faheem Feroze; Saad bin Qamar; Naseem Abbas; Saeed Farooq; Aisha Siddiqui (Journal of Rawalpindi Medical College)
OBJECTIVE: To demonstrate the effective role of Dexmedetomidine as a sedative and analgesic agent in Covid-19 patients when used in conjunction with the established treatment of Acute Respiratory Distress Syndrome.